Charting the regulatory landscape of TP53 on transposable elements in cancer - Qu, Xuan; Liang, Yonghao; McCornack, Colin; Xing, Xiaoyun; Schmidt, Heather; Tomlinson, Chad; Fronick, Catrina; Belter, Edward A.; Macias-Velasco, Juan F.; Wang, Ting

(untitled) (Genome Research, 2025)
The relationship between TP53 and transposable elements (TEs) has been obscure. Given the important role of TEs in oncogenesis, a comprehensive profiling of TE expression dynamics under the regulation of TP53 provides valuable resources for more clarity in TP53's roles in cancer. In this study, we characterized the TE transcriptomic landscape using long-read RNA-seq and short-read RNA-seq in three cancer cell lines varying only in TP53 genetic status. To identify transcripts that use TEs as potential promoters, we developed a computational pipeline, TEProf3, and identified in total 1942 transcripts with high confidence. Among these TE-derived transcripts, 239 are activated by TP53 and 221 are repressed by TP53. These TP53-responsive TE-derived transcripts are mainly driven by members of the ERV and LINE families. Following knockdown of wild-type (WT) TP53 expression, rescuing WT TP53 expression allows for partial recovery of the TE expression profile observed in the context of chronic TP53 expression. TP53 mutations R175H and R273H manifest their oncogenic characteristic partially through activating TE promoters in a cell type–specific manner. Lastly, we identified important sequence motifs that help govern the interactions between TEs and TP53, where TP53 activates TEs with TP53 binding motifs through direct binding and represses TEs indirectly via other pathways. Overall, we present a comprehensive profiling of the impact of TP53 on the activity of TE-derived promoters in isogenic cancer cell lines and provide a high-confidence TE expression atlas of TE promoters that are direct and indirect targets of TP53.